Mooswa & Others of the Boundaries - Fraser, William Alexander, 1859-1933; Heming, Arthur, 1871-1940 (Salt Lake City, UT : Project Gutenberg, 2013)
"Mooswa & Others of the Boundaries" by William Alexander Fraser is a collection of stories written in the early 20th century. The book focuses on the lives and adventures of various woodland animals living in the lush Northern forests of Canada, particularly through the perspective of Mooswa, the Moose, and his fellow creatures. The narrative intertwines their communal experiences, struggles, and interactions with both nature and human threats, emphasizing themes of survival and cooperation among the animal kingdom. At the start of the narrative, we are introduced to the character Mooswa and his friends in the "Boundaries," a vibrant natural world rich with flora and fauna. An important event is preparing for their annual meeting where they will choose a king and discuss matters affecting their lives. The initial assembly brings forth dynamic characters like the clever Black Fox and the comical Whisky-Jack, providing glimpses into their personalities and relationships. Here, we learn about their daily lives, their fears of human trappers, and the cultural importance of the natural law that governs their existence, setting the stage for the conflicts and adventures that will unfold throughout the collection. (This is an automatically generated summary.)
Release date is 2013-02-27
Produced by Al Haines
Keywords: Animals -- Fiction; Canada -- Fiction